Keberlanjutan Program One Village One Product melalui Manajemen Koperasi Tani Mertanadi di Desa Pelaga, Kecamatan Petang, Kabupaten Badung - KUMARANANDA, I GEDE VIBHUTI; SUTJIPTA, NYOMAN; ANGGRENI, I G A A LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018DO - 10.24843/JAA.2018.v07.i04.p14, 2018)
Sustainability of One Village One Product (OVOP) Program Through Mertanadi Farmers Cooperative Management (In the Case of Pelaga Village, Petang Sub-District, Badung Regency) Indonesia's development through village development is one of the government's focus on alleviating poverty in Indonesia. Overcoming the problem of poverty, the government has launched several programs, one of which is to build Indonesia from the village. One of the programs to build Indonesia from the village is the One Village One Product (OVOP) program. It is a regional potential development approach in one region to produce one global class product by utilizing local resources. One of the successful villages in running the OVOP program is Pelaga Village located in Petang Sub-District, Badung Regency. This study aims to determine the sustainability of the OVOP program through the management of Mertanadi Farmers' Cooperative and to investigate the constraints that occur in the management of Mertanadi Farmers' Cooperative. Data collection was done by distributing questionnaires to determine the members' assessment on the sustainability of the OVOP program and using the interview guidelines to find out the management of Mertanadi Farmers' Cooperative. Then the data was analyzed by qualitative descriptive analysis method, which was presented in quantitative analysis. The results of the research showed that the sustainability of the OVOP program through the management of Mertanadi Farmers Cooperative in Pelaga Village, Petang Sub-district, Badung Regency obtained a score of 4.00 with a percentage of 80% that it can be categorized as in the successful category. Technical, social, and economic constraints need to be anticipated to maintain the sustainability of the OVOP program.